2023
DOI: 10.1371/journal.pone.0283682
|View full text |Cite
|
Sign up to set email alerts
|

Selecting police super-recognisers

Abstract: People vary in their ability to recognise faces. These individual differences are consistent over time, heritable and associated with brain anatomy. This implies that face identity processing can be improved in applied settings by selecting high performers–‘super-recognisers’ (SRs)–but these selection processes are rarely available for scientific scrutiny. Here we report an ‘end-to-end’ selection process used to establish an SR ‘unit’ in a large police force. Australian police officers (n = 1600) completed 3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“… Russell, Duchaine, and Nakayama (2009) initially coined the term SR when they documented the exceptional abilities of four individuals in various tasks such as matching unfamiliar faces, remembering unfamiliar faces, and identifying celebrities based on their childhood photographs. Despite limited knowledge concerning the abilities of SRs, law enforcement agencies internationally are increasingly interested in their deployment to improve their operations ( Dunn, Towler, Kemp, & White, 2023 ; Hucklenbroich, 2023 ; Mayer & Ramon, 2023 ; Moreton, Pike, & Havard, 2019 ; Ramon, Bobak, & White, 2019a ; Ramon, Bobak, & White, 2019b ; Ramon, 2021 ; rbb Ferneshen Berlin, 2023 ). In the last decade, research into SRs has increased, particularly investigating how they should be identified ( Ramon, 2021 ), and the nature or underlying mechanisms of their unique ability ( Linka, Broda, Alsheimer, de Haas, & Ramon, 2022 ; Nador, Vomland, Thielgen, & Ramon, 2022 ; Nador, Zoia, Pachai, & Ramon, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Russell, Duchaine, and Nakayama (2009) initially coined the term SR when they documented the exceptional abilities of four individuals in various tasks such as matching unfamiliar faces, remembering unfamiliar faces, and identifying celebrities based on their childhood photographs. Despite limited knowledge concerning the abilities of SRs, law enforcement agencies internationally are increasingly interested in their deployment to improve their operations ( Dunn, Towler, Kemp, & White, 2023 ; Hucklenbroich, 2023 ; Mayer & Ramon, 2023 ; Moreton, Pike, & Havard, 2019 ; Ramon, Bobak, & White, 2019a ; Ramon, Bobak, & White, 2019b ; Ramon, 2021 ; rbb Ferneshen Berlin, 2023 ). In the last decade, research into SRs has increased, particularly investigating how they should be identified ( Ramon, 2021 ), and the nature or underlying mechanisms of their unique ability ( Linka, Broda, Alsheimer, de Haas, & Ramon, 2022 ; Nador, Vomland, Thielgen, & Ramon, 2022 ; Nador, Zoia, Pachai, & Ramon, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Super-recognizers represent the upper tail of a continuum of natural variation in people's ability to identify faces, which appears to be strongly heritable 18,19 . As a result, psychologists have argued that super-recognizers provide a route to high levels of accuracy in challenging real-world unfamiliar face identification tasks, and some police organizations recruit super-recognizers for face identification tasks 4,[20][21][22] .…”
mentioning
confidence: 99%